School inclusion and neoliberalism: who serves the logic of normalization, performance and competition? (Olhar de Professor, 2021)
This article, which has a bibliographical character, aims to discuss the school inclusion in relation to the determinations of the neoliberal rationality. Thus, discussions developed by authors as Silveira Bueno (2004), Rigo (2018) and Laval (2019) were used because of their contributions to the debate about the schooling history of people with some deficiency, in addition to the reflections about the neoliberal thought and the relation between school inclusion and neoliberalism. The results reveal that the school inclusion, under the neoliberal perspective, functions as adjustment and normalization device towards the development of individual characteristics which are adequated to the insertion of individuals at the competitive arena of the labor market. However, it is essential to oppose the neoliberal logic, so that the common school is understood as a space of all and for all, which eliminates the educational dualism that selects and excludes.Thereby, it is necessary to surpass the limits of the neoliberal context in order to effectively achieve the inclusive school.
Keywords: School inclusion. Normalization. Neoliberalism.